2009
DOI: 10.1007/s10856-009-3733-1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical examinations on dental implants with porous titanium coating

Abstract: Due to its good biocompatibility, porous titanium is an interesting material for biomedical applications. Bone tissue can grow inside the porous structure and maintain a long and stable connection between the implant and the human bone. To investigate its long term stability, the mechanical behavior of porous titanium was tested under static and dynamic conditions and was compared to human bone tissue. A promising application of this material is the coating of dental implants. A manufacturing technique was dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 15 publications
0
29
0
2
Order By: Relevance
“…This suggested that implants will struggle to perform well against forces in a range similar to that produced by human jaw. Moreover, pore alignment can affect the mechanical properties of porous titanium [10]. Murr et al in 2010 used electron beam melting (EBM) to produce Ti-6Al-4V open cellular foams with different cell wall structures (solid and hollow).…”
Section: Fabrication Methods and Mechanical Evaluation Of Porous Titamentioning
confidence: 99%
See 1 more Smart Citation
“…This suggested that implants will struggle to perform well against forces in a range similar to that produced by human jaw. Moreover, pore alignment can affect the mechanical properties of porous titanium [10]. Murr et al in 2010 used electron beam melting (EBM) to produce Ti-6Al-4V open cellular foams with different cell wall structures (solid and hollow).…”
Section: Fabrication Methods and Mechanical Evaluation Of Porous Titamentioning
confidence: 99%
“…The high Young's modulus of titanium implants leads to stress shielding and inadequate loading of the underlying bone tissue [10]. Since bone is a living tissue which is continuously modified by the bone cells in response to external signals, reduced mechanical loading leads to resorption of bone, implant loosening and ultimately failure, which has particularly been a problem for orthopaedic implants in the past [9].…”
Section: Introductionmentioning
confidence: 99%
“…One way to reduce the elastic modulus of pure bulk Ti so that it more closely matches that of the human bone is by introducing pores. Porous Ti reportedly had bonelike mechanical properties which could resist continuous loading comparable to the loading conditions imposed on the human jaw 3) . Cell culture study showed that porous Ti had good biocompatibility and was conducive to bone cell attachment and proliferation 4) .…”
Section: Introductionmentioning
confidence: 99%
“…Cell culture study showed that porous Ti had good biocompatibility and was conducive to bone cell attachment and proliferation 4) . Bone tissue could grow inside the porous Ti structure and maintain a long and stable connection between the implant and the human bone 3) . Therefore, porous Ti seemed to be a viable candidate for use in dental and biomedical applications, such as implants and tissue-engineering scaffolds [3][4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation